Nurses’ Knowledge in Relation to the Anorexia–Cachexia Syndrome in Cancer Patients: A Cross-National Comparison in Two European Countries - Socratous, Georgia; Cloconi, Constantina; Tsatsou, Ioanna; Charalambous, Andreas (My University, 2021)
Introduction: The Anorexia–Cachexia Syndrome (ACS) is a severe complication of cancer and is considered to be a significant cause of morbidity and mortality affecting up to two-thirds of cancer patients and one that needs specialized nursing care. Studies showed that the ACS has been relatively under-researched and under-resourced whist the nurses’ knowledge has not been systematically explored. Objective: Τo explores nurses’ knowledge, understanding, and management of ACS in clinical practice in two European countries. Methods: Descriptive-comparative study with 197 cancer nurses recruited during two National Conferences in Greece and Cyprus. Data were retrieved with the “Investigation of anorexia–cachexia syndrome in Practice” questionnaire. Results: In terms of nurses’ perceptions on ACS, the prevailing characteristic reported in both countries was anorexia (p =.65) followed by weight loss (p =.04). 189 nurses (95.9%, p =.176) do not currently use a tool to assess patients’ nutritional status as part of their standard clinical practice. Statistically significant differences were found in relation to the routine assessment of nutritional-related symptoms including early satiety (Cyprus 64% vs. Greece 37%, p =.001), hiccough (66% vs. 36%, p <.001), alteration of the taste/odor sensation (77% vs. 45%, p <.001), problems in the oral cavity (84% vs. 68%, p =.032) and daily activities (85% vs. 69%, p =.032). The priority level for the ACS management differed significantly in the two countries (p =.006), with higher priority being reported in Cyprus. Conclusion: The study showed that more education is needed for cancer nurses to better understand the ACS which can facilitate the better management of the syndrome in clinical practice.
Keywords: Anorexia–cachexia syndrome; Management; Nurses’ perceptions; Nurses’ knowledge